UNE AUTRE / L’AUTRE. LES FEMMES DE WOODY ALLEN - Delia NAN (Studia Universitatis Babeș-Bolyai. Philosophia, 2020)
Another/The Other. Woody Allen’s Women. In Woody Allen’s movie, the main character, philosopher and writer, becomes the unseen witness of a few psychotherapy sessions she hears trough the wall. Gradually she becomes the analyzed herself, identifying herself with the patient in the psychotherapist office. She has some disturbing dreams (among them, the most important one presents major conflicts in her life as a play) and the entire process culminates in an existential crisis. The moment of its resolution is followed by the acknowledgement that the patient beyond the wall had decided to end the therapy and will not return.